2016
DOI: 10.1002/chem.201504573
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Formic Acid Dehydrogenation Catalyzed by AlIII–Bis(imino)pyridine

Abstract: The mechanism of formic acid dehydrogenation catalyzed by the bis(imino)pyridine-ligated aluminum hydride complex (PDI(2-))Al(THF)H (PDI=bis(imino)pyridine) was studied by density functional theory calculations. The overall transformation is composed of two stages: catalyst activation and the catalytic cycle. The catalyst activation begins with O-H bond cleavage of HCOOH promoted by aluminum-ligand cooperation, followed by HCOOH-assisted Al-H bond cleavage, and protonation of the imine carbon atom of the bis(i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…[23] Also the last s-bond metathesis step in the cycle seemed questionable.Acomprehensive calculational study, however, demonstrated that the metal hydride mechanism shown in Scheme 1isfeasible. [15,18,[31][32][33][34][35][36][37][38][39][40][41][42] Especially noteworthy are two very recent investigations on LiAlH 4 -catalyzed alkene and aldehyde/ketone hydroboration. Acrucial step is the hydrogenolysis of the metal À Cbond by H 2 ,for which the rate is known to decrease with decreasing bond ionicity:N a À C > Mg À C > Al À C. [25] since it is well-known that RNH 2 and R 2 NH react smoothly with LiAlH 4 to give aluminium amide products and H 2 , [26][27][28][29][30][31] hydrogenolysis of AlÀNbonds to give amines is anticipated to be even more cumbersome.S ubstitution of H 2 for polar borane or silane reductants was therefore al ogical step.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Also the last s-bond metathesis step in the cycle seemed questionable.Acomprehensive calculational study, however, demonstrated that the metal hydride mechanism shown in Scheme 1isfeasible. [15,18,[31][32][33][34][35][36][37][38][39][40][41][42] Especially noteworthy are two very recent investigations on LiAlH 4 -catalyzed alkene and aldehyde/ketone hydroboration. Acrucial step is the hydrogenolysis of the metal À Cbond by H 2 ,for which the rate is known to decrease with decreasing bond ionicity:N a À C > Mg À C > Al À C. [25] since it is well-known that RNH 2 and R 2 NH react smoothly with LiAlH 4 to give aluminium amide products and H 2 , [26][27][28][29][30][31] hydrogenolysis of AlÀNbonds to give amines is anticipated to be even more cumbersome.S ubstitution of H 2 for polar borane or silane reductants was therefore al ogical step.…”
mentioning
confidence: 99%
“…Indeed, hydroboration and hydrosilylation reactions were found to be more promising. [15,41,42] Herein, we introduce LiAlH 4 , which is normally applied as astoichiometric reducing agent, as as imple catalyst for imine reduction using the bulk commodity H 2 at ac onvenient 1bar pressure (Table 1). [15,18,[31][32][33][34][35][36][37][38][39][40][41][42] Especially noteworthy are two very recent investigations on LiAlH 4 -catalyzed alkene and aldehyde/ketone hydroboration.…”
mentioning
confidence: 99%
“…Essentially a reverse reaction to the CO 2 reduction discussed above is the recently reported aluminum‐catalyzed dehydrogenation of formic acid to H 2 and CO 2 using Al catalyst 15 (Scheme ) . An “aluminum‐ligand cooperative activation” operative mechanism was proposed on the basis of experimental data and DFT calculations . The initial turnover frequency is high with 5200 h −1 , and this work is of interest with regards to hydrogen storage.…”
Section: Introductionmentioning
confidence: 82%
“…According to the analysis of NMR, IR, and X‐ray, a plausible mechanism was proposed to proceed via an Al‐(OOCH) 2 species (unlike other monoformate intermediates) followed by β‐hydride elimination and FA‐enabled protonation (Scheme ). Further insights about these mechanistic pathways have been scrutinized computationally by Yu and Fu …”
Section: Catalysts With a Pincer‐type Ligandmentioning
confidence: 99%
“…Further insights about these mechanistic pathways have been scrutinized computationally by Yu and Fu. [40] Enthaler's group reported the first Ni-based PCP pincer complex 20 for the FA decomposition to CO 2 and H 2 with the TON of up to 626 (Figure 7). [25b] However, the efficiency is not as good as those of others complexes.…”
Section: Catalysts With a Pincer-type Ligandmentioning
confidence: 99%